2016
DOI: 10.1002/cjce.22575
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the effects of SnO2 nanoparticles and KCl salt on a water base drilling fluid properties

Abstract: Reduction of proven gas and oil reserves and increasing demand for energy forces the petroleum industry to drill deeper and more complicated wells. Drilling in these harsh environments requires drilling fluids with specific characteristics. So, improvement of the drilling fluids that can act as proper fluids at high pressure and high temperature conditions is vital in the drilling industry. The purpose of this study is examining the effects of SnO2 nanoparticles on the properties of drilling fluids and determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 61 publications
1
23
0
Order By: Relevance
“…HP/HT filtration after aging indicated that the 0.00285 wt % (0.01 ppb) of MWCNTs was the optimal concentration with the lowest filtration volume (Figure 14). Parizad and Shahbazi [46] investigated the effects of Tin oxide (SnO2) NP on water-based drilling fluid properties. They concluded that adding SnO2 NP enhanced the characteristics of the drilling fluids such as rheology, thermal and electrical conductivities, thixotropy and filtration characteristics.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…HP/HT filtration after aging indicated that the 0.00285 wt % (0.01 ppb) of MWCNTs was the optimal concentration with the lowest filtration volume (Figure 14). Parizad and Shahbazi [46] investigated the effects of Tin oxide (SnO2) NP on water-based drilling fluid properties. They concluded that adding SnO2 NP enhanced the characteristics of the drilling fluids such as rheology, thermal and electrical conductivities, thixotropy and filtration characteristics.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…In the third phase, 0.5 wt% nano-silica was stirred with the mud for 2 h to further reduce the water loss of the mud by plugging the nano-pores of wellbores [30]. In the fourth phase, a large amount of ions were supplied by stirring 3 wt% potassium chloride with the mud for 2 h. By balancing the charge of clay and polymers, the stability of drilling fluids can further improve [31]. Four drilling fluids, such as 1#, 3#, 5# and 7#, were prepared in this way.…”
Section: Preparation Of Drilling Fluidsmentioning
confidence: 99%
“…Nanomaterials play a multifunctional role in the drilling and completion process, especially in complex formations and extreme environments, such as high‐temperature deep wells. There exist several advantages by adding nanomaterials into drilling and completion fluids Stabilizing wellbore .…”
Section: Introductionmentioning
confidence: 99%
“…Stabilize wellbore; reduce filter loss; improve rheology; increase thermal stability Alimohammadi et al, [14] Sharma et al, [15] Parizad and Shahbazi, [16] Ehtesabi et al, [17] Qiu, [18] and Di et al [19] 2. Change the wettability of porous surfaces of sandstone 3.…”
Section: Nanofluidmentioning
confidence: 99%
See 1 more Smart Citation